SOSIALISASI DAN IMPLEMENTASI PENANGANAN TRANSAKSI DAN AKAD SYARIAH PADA MAJLIS TA’LIM AN NISA JLN BAKUNG 04 KEL.LOWOKWARU KOTA MALANG - Muwidha Muwidha; Mahmudatul Himma; Basuki Basuki; Yusna Yusna (Jurnal Pengabdian kepada Masyarakat, 2020)
The purpose of this Community Service Activity (PkM) is in the context of providing counseling, socialization and implementation to the public regarding sharia business transaction contracts to female members of the majlis ta'lim An-Nisa. In the beginning, the implementation will be carried out at the house of Jln. Daffodil 04 Lowokwaru Malang City. Because the pandemic period was finally based on the coordination of the PkM team, the Chairperson of the Majlis Ta'lim An-Nisa and the Takmir of the Fadhilah Mosque, the activities were carried out at the mosque by taking a schedule after the dawn congregation on Tuesday, August 18 and 25 2020. Hours 5:00 to 7:00. The number of participants was 46 people consisting of fathers and mothers.At the time of implementation, the material planned was presented smoothly. This material is considered important because to start a business based on sharia, the type and validity of transactions need to be properly understood. When the transaction is understood, then choose various sharia contract offerings to suit the needs of doing business.According to an Islamic perspective, Islamic law is created and implemented as a whole for nothing but the purpose of the benefit and welfare of the people in this world and the hereafter. To achieve this goal, Islamic law has several principles that underlie the implementation of these objectives, namely: 1) providing convenience and eliminating difficulties, 2) minimizing the burden, and 3) taking the path of stages.The findings and experiences in the implementation of PkM are expected to be a further phase to build awareness about being a true Muslim. Not only diligent in worshiping Allah (mahdhoh) but also have to build a better muammalah. Because in essence Islam, many teachings regulate how mu'ammalah is practiced more masive. Islam is a guidance for the creation of peace. Prosperity can be created if the community is relatively aware of and understands the level of welfare and the simplest measure of well-being is the adequacy of life and this certainly talks about the path of rizki and economic welfare.